Determinants of Tree Planting and Cover Retention in Arid and Semi-Arid Areas of East Africa: The Case of Machakos County, Kenya - Mutuku, Heeran M.; Kiruki, Harun M. (European Scientific Journal, ESJ, 2023)
Rapid human population growth, increased demand for land, overexploitation and the degradation of local natural resources have led to serious socio-economic and environmental challenges in Machakos County, Kenya, East Africa. This has led to a drastic reduction in tree cover in arid and semiarid areas over the years. To reverse this trend it is important to understand the socio-economic factors that determine household tree planting and cover retention in Machakos County. Based on a structured questionnaire targeting 412 respondents as well as focus group discussions and key informants, we assessed the determinants of tree planting cover retention using a logistic regression model. The study found that socioeconomic variables that significantly influenced tree cover adoption in Machakos County in Kenya included gender (p=0.011), household size (p=0.030), and title deed ownership (p=0.023). The respondents used tree products to enhance their socio-economic resilience. In total, 58 different types of tree species were planted or retained on the farms. The major tree species included Eucalyptus saligna, Grevillea robusta, Mangifera indica, Persea americana, Croton megalocarpus, and Terminalia brownie. Based on our findings we recommend more involvement of women and youth in tree planting activities in Matungulu Sub-county.